Using micro silica bead TLDs in high dose rate brachytherapy dosimetry: A phantom study. (February 2022) - Babaloui, Somayyeh; Jafari, Shakardokht; Palmer, Antony L.; Polak, Wojciech; Sheidaei, Ali; Shirazi, Alireza; Lohstroh, Annika; Jaberi, Ramin
Abstract: In vivo dosimetry (IVD) is a powerful method for treatment dose verification which has been applied in brachytherapy (BT) using different dosimetry systems and technologies. However, implementation of IVD in routine clinical workflow and patient quality control is limited in many departments. This is due to challenges related to the high gradient dose distribution, large dose range and dose rate around BT sources. The apparent lack of utilization of high accuracy IVD systems, which are straightforward to use in a clinic, is currently a significant missed opportunity for quality and safety assurance. Commercial silica bead thermoluminescent dosimeters (TLDs) (Jafari et al., 2014a, 2014b) appear suitable for IVD in high dose rate (HDR) BT. The dose response of silica bead TLDs was characterized in a water phantom and a constructed anthropomorphic pelvis phantom by exposing them with 60 Co source as the used source in our BT department. Also dose response of bead TLDs was defined in a CTDI phantom with 120 kV energy exposure. It was found that measured dose differences to planning system calculations varied from −2.0% to 2.9% during pelvis phantom investigations. Mean experimental dose differences did not exceed the standard uncertainty 7.0% (k = 2) estimated for this study. The phantom results presented indicate that silica beads TLDs may be used to provide in vivo verification of delivered dose in intracavitary HDR BT although this work verifies use only for 60 Co source. Highlights: Dosimetric response of bead TLDs was evaluated for 60 Co HDR brachytherapy source(s). Dose differences of bead TLDs to TPS varied from −2.0% to 2.9% in phantom dosimetry. Dosimetric response of bead TLDs was evaluated in a CTDI phantom by exposing to 120 kV.